El apoyo familiar en el proceso de integración educativa de estudiantes con necesidades educativas en condición de discapacidad - Angélica Fontana-Hernández; Ana Laura Alvarado-Valverde; Mauren Angulo-Ramírez; Elizabeth Marín-Valverde; Dania Melissa Quirós-Salas (Revista Electrónica Educare)
In the process of socialization, the family has a fundamental role in the care and raising of the children, but principally, in the transmission of knowledge, values and customs that allow them to adapt to the society as active and productive individuals. In the last years, the Costa Rican educational system has experienced significant changes, due to the processes of students’ school integration, who present educational needs, because they need specialized supports and different resources for their formation and integral development. Thus, a concern was generated so that the familiar support is investigating in the process of students’ school integration, who are the ones who receive significant curricular adaptations in the public schools, and for instance, it was necessary to determine the kind of supports that are provided to the members of the family, as well as, the ways in which these supports can benefit the process of school integration.